Lacosamide at therapeutic concentrations induces histone hyperacetylation in vitro - Granit, Avital (Epilepsia Open, 2018)
Inhibition of histone deacetylases (HDACs) and subsequent hyperacetylation of histone proteins lead to altered gene expression associated with therapeutic drug effects, but also with teratogenicity. The only US Food and Drug Administration (FDA)–approved antiepileptic drug that has been consistently shown to induce histone hyperacetylation is valproic acid. More recently, lacosamide was reported to interfere with histone modifications, but histone hyperacetylation was not demonstrated. In the current study we evaluated the effects of lacosamide on histone acetylation in vitro. MDA‐MB‐231 (triple‐negative breast cancer) cells and human placental BeWo cells were exposed for 16 hours to 5‐20 μg/ml (20‐80 μm) lacosamide. Histone acetylation was evaluated by western blot analysis. We additionally measured HDAC1 activity in the presence of lacosamide. At 5, 10, and 20 μg/ml, lacosamide enhanced histone acetylation in BeWo cells by 1.7‐fold (p > 0.05), 3.4‐fold (p < 0.05), and 3.0‐fold (p > 0.05), respectively. Histone H3 acetylation and total histones H3 and H4 levels were not significantly modified (p > 0.05). The magnitude of change in histone acetylation in MDA‐MB‐231 cells was smaller (p > 0.05). In contrast to valproic acid, lacosamide did not inhibit HDAC1. Our findings suggest that the effects of lacosamide on gene expression, and the related potential antitumor activity and teratogenicity, may differ from those of valproic acid.